Factors Influencing Healthcare Workers' Ability to Prevent Malpractice - Mangesti, Yovita Arie; Asmara, Gregorius Yoga Panji (Penerbit Goodwood, 2026)
Objective: This study aims to understand how transformational leadership, reward systems, and emotional intelligence can help prevent malpractice in healthcare. Methodology/Approach: This study used a qualitative phenomenological approach conducted at a referral hospital. Data were collected through in-depth interviews with physicians, health workers, managers, and members of the hospital's ethics and legal committee, as well as through direct observation. Results/findings: Based on the study findings, a reward system based on safety, leadership transformative, and emotional intelligence Intelligence (EI) healthcare workers work together to create a culture of patient safety. Employees are encouraged to report concerns without fear. Because leadership transformative push A psychologically safe environment. Non-material rewards that encourage adherence to procedures are used in safety-based reward systems to reinforce positive behaviors. Emotional intelligence (EI) improves ethical decision-making, communication, and emotional control. The integration of these three elements has been shown to strengthen the overall safety culture by improving incident reporting, interdisciplinary collaboration, and patient trust and satisfaction. Conclusion: Transformative leadership, a fair reward system, and strong emotional intelligence are key elements in minimizing the risk of malpractice and improving the quality of healthcare services. Limitations: This study was limited to a small number of hospitals and relied on qualitative data, which may not be representative of all healthcare settings. Contribution: This study contributes to the development of management strategies in healthcare, particularly in leadership training, reward system design, and enhancing emotional.